The Problem of the Jakarta High Court Decision Number 10 /Pid.Sus-Tpk/2021/pt DKI Against Dr. Pinangki Sirna Malasari, S. H., M. H - Rahmah, Nur (Faculty of Sharia, IAIN Metro, 2023)
Corruption is an extraordinary crime, and efforts to eradicate it must be taken seriously. In deciding corruption cases, judges must consider the consequences of the defendant's actions. Judges can decide cases, but this freedom is not absolute; the community must consider it. Thus, judges cannot act arbitrarily in deciding cases. Decree Number 10/Pid.Sus-TPK/2021/PT DKI regarding corruption cases committed by the Pinangki Prosecutor's Office has juridical considerations regarding the gender of the accused, which is used as one of the reasons for the reduction. The duration of detention is from 10 to 4 years. Therefore, many parties consider the consideration and consideration of Decision Number 10/Pid.Sus-TPK/2021/PT DKI is wrong. This study aims to analyze the validity of judges' decisions based on criminal liability and the validity of judges' rulings and court decisions. The results of this study show that the judge's consideration and verdict against the Pinangki Public Prosecutor are unreasonable.